The Anticancer Activity of Cetraria Islandica (L.) Ach in Breast Cancer Cells Through Crosstalk of Ampk-α1 and Erk1/2 Signalling - Celal Güven; Eylem Taskın; Onder Yumtutas; Leyla Turker Sener; Yusuf Ozay; Fulya Dal; Mufide Ahbab; Ibrahim Bozgeyik; Isil Albeniz; Haydar Bagıs; Atilla Yıldız (Turkish Journal of Agriculture: Food Science and Technology)
In the present study, we aimed to evaluate the anticancer activities of Cetraria islandica (C.islandica) extracts on MCF-7 breast cancer cell lines. Cell viability, protein levels, apoptotic cells number, F-actin distribution were measured. Cell viability of MCF-7 breast cancer cells was found to be reduced in a dose-dependent manner.EC50 values of C.islandica on MCF-7 cells were found to be 9.2047 E-5 g/ml (cell amount) by using intelligence system. Expressions of p53, caspase 3 and Bcl-2, were shown to be elevated after low doses of extract and diminished after high dose treatments. PPAR- protein level was decreased, although AMP-activated kinases-α1 (AMPK-α1) protein level was increasedin its extract groups. ERK1/2 protein level was also elevated in its extract groups. 125 mg/ml of extract treated cells show a low decrease in actin filament density. MCF-7 cells with C.islandica treatment for 24 h increased the apoptotic cell percentage, though the cells-treated with C.islandica for 48 was high necrotic cells percentage. Consequently, the C.islandica extract treatment causes to elevate ERK1/2 and AMPK-α1 protein levels, resulting in PPAR- and then triggers the apoptosis by modulation caspase-3 and P53 protein levels. Therefore, C.islandica might be a good candidate for anticancer tissue, especially soft tissue tumours.